(untitled) (Bangladesh Journal of Medical Education, 2014)
Job satisfaction includes the fulfillment of both extrinsic and intrinsic satisfaction dimensions.. To find out the views of medical teachers regarding their job satisfaction this study was carried out in 10 medical colleges for one year among 218 teachers working in preclinical, paraclinical and clinical departments of those medical colleges. Structured questionnaire using 47 characters related to job satisfaction were compiled under 8 themes. Among these for 39 questions 5 point Likert scale was used as rating scale .For satisfaction or dissatisfaction 3 was taken as the cut off value. Mean age of the respondents were 42 years and they passed 3 years after last promotion, 41% teachers were female , 87% were married and 81 % had post graduate degrees. Among the 8 themes teachers were highly satisfied with all of the 4 items under theme 1( relation with others). Teachers were also satisfied with theme 2 (teaching related responsibilities )& theme 3 ( teaching environment) though level of satisfaction was not very high. Teachers were not satisfied with activities related to current work ie, theme 4 but highly dissatisfied with the facilities available other than the salary ( theme5). Regarding local administration medical teachers were highly dissatisfied (theme 6) but there was low level satisfaction with central administration (theme7). Regarding clinical teachers satisfaction all teachers were highly satisfied with all the items (theme 8). Satisfaction with one or other aspect of their job was 58.6% which was not very high. Low salary , adverse environment, political interference in posting promotion was the most important cause for dissatisfaction. DOI: http://dx.doi.org/10.3329/bjme.v2i1.18133 Bangladesh Journal of Medical Education Vol.2(1) 2011: 18-22